WHY PAIN ??? - Patel, Shahil (Journal of Medical Biomedical and Applied Sciences, 2017)
Most of us are having trouble like pain either at the starting of our day while wake-up from bed either due to lack of sleep/ inadequate diet and water etc. or at the end of our work while moving from office and/ or at the home after having terrible work at home as compare to office work.